2009
DOI: 10.1088/0004-637x/704/1/513
|View full text |Cite
|
Sign up to set email alerts
|

The Radial Velocity Tatooine Search for Circumbinary Planets: Planet Detection Limits for a Sample of Double-Lined Binary Stars—initial Results From Keck I/Hires, Shane/Cat/Hamspec, and TNG/Sarg Observations

Abstract: We present preliminary results of the first and on-going radial velocity survey for circumbinary planets. With a novel radial velocity technique employing an iodine absorption cell, we achieve an unprecedented radial velocity (RV) precision of up to 2 m s −1 for double-lined binary stars. The high-resolution spectra collected with the Keck I/Hires, TNG/Sarg, and Shane/CAT/Hamspec telescopes/spectrographs over the years 2003-2008 allow us to derive RVs and compute planet detection limits for 10 double-lined bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…It has been suggested that at least some of these planets might have formed as second-generation planets from ejected stellar material after the common-envelope phase (Perets 2010). Efforts are also made to search for circumbinary planets with Doppler spectroscopy (Konacki et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that at least some of these planets might have formed as second-generation planets from ejected stellar material after the common-envelope phase (Perets 2010). Efforts are also made to search for circumbinary planets with Doppler spectroscopy (Konacki et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The problem is that the spectra of close binary stars are highly variable due to their orbital motion which typically leads to relatively large velocity uncertainties. However, the TATOOINE radial velocity survey (Konacki et al 2009) is searching for planets around double-lined spectroscopic binaries and has reached precisions of a few m s −1 , comparable to, albeit not as good as, precisions reached for single stars. Although Konacki et al (2009) have yet to report a circumbinary planet and their sample size is small (10 systems), their work demonstrates that future planet searches may be performed on close binaries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the TATOOINE radial velocity survey (Konacki et al 2009) is searching for planets around double-lined spectroscopic binaries and has reached precisions of a few m s −1 , comparable to, albeit not as good as, precisions reached for single stars. Although Konacki et al (2009) have yet to report a circumbinary planet and their sample size is small (10 systems), their work demonstrates that future planet searches may be performed on close binaries. Duquennoy & Mayor (1991) estimate that 57% of G stars may be in multiple systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three principal techniques are: (i) precise radialvelocity (hereafter RV) measurements to detect the wobble of the binary mass center (Konacki et al 2009), (ii) photometric detection of transits of the planet(s) across the disks of the components of the inner binary (Doyle et al 2011), and (iii) timing of the inner binary eclipses (Lee et al 2009). …”
Section: Introductionmentioning
confidence: 99%